Security dilemma: Upholding Indonesia's independence and active foreign policy - Azwar Amar Ma'ruf; Helda Risman (Strategi Perang Semesta, 2022)
The world condition where there has been a war between Russia and Ukraine and the involvement of the US has had a drastic impact on the international political system. As the two superpowers in the world today and not forgetting about China, Indonesia which has Independence and an Active Foreign Policy must face this challenge whether to choose one side or remain as a non-aligned movement country. This research focuses on the point of view where Indonesia is in a security dilemma between remaining as a non-aligned movement country or choosing to side with one of these superpowers.